Digital agroclimatic plot: Advancing climate-smart agriculture, applied learning, and innovation - Ramos Solorzano, Gresia Dalal; Jimenez Rodas, Daniel Ricardo; Arce Gomez, Daniela; Lizarazo Torres, Miguel Angel (2025)
Since its inception in 2022, the Digital Agroclimatic Plot has evolved into a comprehensive living laboratory that integrates innovation, applied learning, and climate-smart agriculture in Guatemala’s Dry Corridor, one of the regions most exposed to climate variability, drought, and production risks. This initiative was intentionally designed to respond to the real and immediate needs of its users, including students, faculty from CUNORI University, and local farmers, by generating accessible and actionable agroclimatic information to support evidence-based decision-making. In this video, viewers are guided through the different components of the Digital Agroclimatic Plot, including the network of agroclimatic sensors, field trials of climate-smart agricultural practices, and the use of modern technologies such as drone-based spraying equipment. Beyond showcasing tools and technologies, the video highlights how this space strengthens hands-on learning, bridges theory and practice, and fosters collaboration between academia and farming communities. Through user experiences and field-based insights, the Digital Agroclimatic Plot emerges as a model for building resilient, sustainable, and knowledge-driven agricultural systems in climate-vulnerable contexts.